TINJUAN PELAKSANAAN PEKERJAAN PENINGKATAN JALAN OVERLAY HOTMIX PADA RUAS JALAN GANDU – PANONGAN 1 - Muryadi, raden (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
Gandu-Panongan 1 road is one part of the connecting road between the gandu village in dawuan sub-district to panongan village in jatitujuh sub-district gandu panongan 1 road uses a flexible pavement structure that uses asphalt as an aggregate binding material so that it has a relatively flexible road structure, resulting from the research on the implementation of the improvement of the gandu-panongan road later it is hoped that it can be used as comparative data to carry out road improvement works both government or private institutions, the pavement implementation of the gandu-panongan1 road work uses asphalt mixing plant with a thickness of 40 mm or 4 cm.